Controle de perda de circulação em perfuração de poços de petróleo utilizando material fibroso derivado da Moringa oleifera Lam - Silva, José Valdo da (2018)
The oil and gas industry has been making efforts to develop technologies and techniques for drilling wells. Several challenges are faced by drilling companies in Brazil. Among these, the fight against the loss of circulation in permeable rock formations, which is a common scenario in the drilling of Brazilian wells. In this context, this work aims to describe a new additive for water based fluid, designed to form an effective barrier and low permeability in areas of loss of circulation, as well as characterize and evaluate the effectiveness of fibrous materials derived from Moringa Oleífera Lam (MoLAM), in combating the loss of circulation in permeable and producing zones. Initially the characterization of the studied materials was carried out, such as: Thermogravimetric Analysis (TG), Differential Exploration Calorimetry (DSC) and Scanning Electron Microscopy (SEM). Then, invasion of the water-based fluid containing the MoLAMderived LCMs and their plaster forming capacity under different operating conditions was evaluated on a 100 psi pressure acrylic column using 20/40 sand and (No. 1) as filter media and fibrous materials derived from MoLAM, pie, pod sponge, stem and seedless pod, and the commercial materials Fracseal and Soluflake as the sealant medium. The performance of each LCM sample was determined based on the amount of filtrate in the filter media, according to the American Petroleum Institute (API) standard. The results obtained showed that the amount of fluid loss depends on the LCM, concentration and particle size distribution. From the data obtained it was possible to identify that between the four LCMs, the pie and the pod had better results to control loss by infiltration, presenting an invasion of infiltration in the rock between 4 and 5 cm and presented the best results in loss control in the value of 17ppb for both, but for the control of partial or total loss the four materials presented positive results forming a total plug of the flow in the interval of 30 minutes in the concentration of 20 to 28 ppb, being the material Fracseal was with 50 ppb and Soluflake at 35 ppb. Laboratory tests have shown that the invasion of fluid is greatly reduced when using this system. This brings several important benefits, such as reduced differential lock, return permeability results and therefore good performance indications. In addition to being one of the potential technical solutions, they have environmental properties from renewable sources.